Formulation and evaluation of phytosomes containing bioactive from Carica papaya seeds - Patil, Rima R; Pingale, Prashant L; Upasani, Chandrashekhar D (Creative Pharma Assent, 2024)
Background: Papaya seeds are a rich source of proteins, fat, fibers, vitamins, minerals, monounsaturated fatty acids, polyphenols, and powerful antioxidants like flavonoids. Low solubility limits the absorption and bioavailability of herbal constituents. Hence, phytosomes of Papaya seed extract were formulated to enhance its solubility and bioavailability. Methodology: Papaya seeds were extracted using ethanol as solvent, and all the phytoconstituents present in the extract were assessed during the phytochemical screening and LC-MS analysis. In-vitro antidiabetic activity pure extract was determined by alpha-amylase and alpha-glucosidase enzyme inhibitory assay. The phytosomes of extract were formulated using the lipid thin film formation method and Soya lecithin and Cholesterol as lipids. The formulated phytosomes were analyzed for parameters such as particle size, zeta potential, encapsulation efficiency, percent drug content, and In-vitro dissolution study. The chemical nature of the formulation was studied using FTIR analysis and powder X-ray diffractometry. Thermal stability of phytosomes analyzed with the help of Differential Scanning calorimetry. Results: LC-MS identified 16 phytoconstituents. In-vitro antidiabetic activity showed 59.97% and 51.17% inhibition of enzymes alpha-amylase and alpha-glucosidase, respectively. The encapsulation efficiency of the optimized formulation was 88.41±0.91% with a particle size of 188.0±53.7nm. TEM images of formulation confirm the formation of phytosomes. FTIR, DSC, and Powder X-ray diffractometry showed no unwanted peaks. The in vitro dissolution study showed 89.26±1.05% CDR of phytosome, while the extract showed 47.78±0.59% CDR. Conclusion: Evaluation results of phytosomes suggest that this formulation can be used as an effective herbal antidiabetic formulation